Investigation of Grooved Circular Jet Flow Experimentally and Using Computational Fluid Dynamics - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2015)
This study is the investigation of grooved circular jet flow experimentally and using computational fluid dynamics (CFD). Experimental studies were conducted by using straight circular and grooved circular tubes in a multi-purpose low-range subsonic wind tunnel. Single channel hot wire anemometer was used in turbulence measurements. Numerical studies for the solution of jet flow were performed through FLUENT program (ANSYS 14.5). Jet flow profiles at different velocities were formed by using the data generated at predetermined stations in the experiment room for the straight circular tubes and grooved circular tubes. After transferring the experimental data to Fluent, jet exit points of the circular tubes were placed in the quarter model to coincide with the initial coordinates of experimental room. CFD Calculations were done by implementing different velocities in the experimental room and the jet. Jet flow structures obtained from both computational and experimental calculations are shown in graphs and the data is presented in Tables. The obtained parameters are as follows: axis velocity (U-e), root mean square velocity (U-rms), turbulence velocity (U-turb), jet half width (b) and Reynolds numbers (Re-D and Re-b). These parameters were calculated with reference to jet radius and jet half width. Graphics formed by the generated non-dimensional data were compared to the previous studies.